PESAN DAKWAH DALAM TRADISI MAUDU’ LOMPOA DI DESA CIKOANG KECAMATAN MANAGARABOMBANG KABUPATEN TAKALAR - Achmad Badawi Alfarezi; M. Ishaq Shamad; Ratika Nengsi; Nur Setiawati; Andi Hasriani (STKIP Subang, 2025)
This study aims to describe the Maudu’ Lompoa celebration process and explore the da’wah messages embedded within it. Conducted in Cikoang Village, Mangarabombang District, Takalar Regency, this research adopts a qualitative method with a phenomenological approach, utilizing interviews, observation, and documentation for data collection, and applying data reduction, presentation, and conclusion techniques for analysis. The findings reveal that the Maudu’ Lompoa tradition carries significant da’wah messages. It emphasizes the reinforcement of tawhid and includes the recitation of a’ratek/azzikkiri’ during the Prophet Muhammad’s birthday commemoration as a reflection of love and reverence toward the Prophet. The celebration reminds the community of the Prophet’s mission, including tawhid, rahmatan lil ‘alamin, and Islamic moral teachings. It also preserves local Islamic traditions by incorporating da’wah into cultural forms such as pamanca’ (martial arts), pakarena decorative elements, and julung-julung boats, symbolizing Islamic propagation blended with local identity—an example of Islamic inculturation that retains its spiritual essence. The tradition fosters strong solidarity and brotherhood among local residents and diaspora, reinforcing ukhuwah Islamiyah and ukhuwah wathaniyah, while also enhancing silaturahmi as a form of da’wah bil hal. Furthermore, Maudu’ Lompoa functions as an educational medium for youth through religious events, competitions, and Maulid recitations that promote the internalization of Islamic values. It also symbolizes the continuity of Islam in local history, with Cikoang recognized as a historical center for Islamic propagation by Sayyid Jalaluddin Al-Aidid, whose teachings are preserved through generations. Thus, Maudu’ Lompoa serves as a comprehensive platform for cultural, spiritual, and educational da’wah.